The impact of the climate crisis on gender inequality. Looking to the frontlines in search of priorities for policy - Castelo, Sofia; Antunes, Lia; Ashrafuzzaman, Md. (Frontiers in Sustainable Cities, 2024)
The climate crisis disproportionately impacts women and girls all over the world. To understand what the priorities in terms of policy are, an examination is conducted on the impacts taking place in South Asia (focusing on the countries of Bangladesh, India, and Pakistan), an area of the globe that is highly vulnerable to climate change and is characterized by having strong patriarchal values. Gender stereotypes and roles in the region heighten women and girls' vulnerability to climate impacts, both in general and in situations of crisis resulting from extreme weather events. Deepening the understanding of the climate crisis' impact on gender in South Asia, a region at the frontline of these effects, can assist in reaching a baseline understanding of the challenge from a global perspective. Methodologically, we reviewed an extensive body of literature, both specialty books and scientific articles, recent institutional reports as well as news or journalistic reports from reliable international press. In this research, the argument is made that today, climate action and urban development cannot be considered separately from women's rights. Extensive scientific data and research support the integration of a gender perspective in urban adaptation standard practices, and priorities in terms of policy to safeguard women and girls are identified accordingly. The allocation of half of climate funds, including those of loss and damage, directly to women or women-led organizations is identified as being particularly relevant. Bold and ambitious policymaking is urgently needed to build capacity to face the multiple crises unfolding.